Individual and social factors affecting the ability of American crows to solve and master a string pulling task. (30th December 2019) - Pendergraft, LomaJohn T.; Lehnert, Adrienne L.; Marzluff, John M.
Abstract: Crows and other birds in the family Corvidae regularly share information to learn the identity and whereabouts of dangerous predators, but can they use social learning to solve a novel task for a food reward? Here, we examined the factors affecting the ability of 27 wild‐caught American crows to solve a common string pulling task in a laboratory setting. We split crows into two groups; one group was given the task after repeatedly observing a conspecific model the solution and the other solved in the absence of conspecific models. We recorded the crows' estimated age, sex, size, body condition, level of nervousness, and brain volume using DICOM images from a CT scan. Although none of these variables were statistically significant, crows without a conspecific model and large brain volumes consistently mastered the task in the minimum number of days, whereas those with conspecific models and smaller brain volumes required varying and sometimes a substantial number of days to master the task. We found indirect evidence that body condition might also be important for motivating crows to solve the task. Crows with conspecific models were no more likely to initially solve the task than those working the puzzle without social information, but those that mastered the task usually copied the method most frequently demonstrated by their knowledgeable neighbors. These findings suggest that brain volume and possibly body condition may be factors in learning new tasks and that crows can use social learning to refine their ability to obtain a novel food source, although they must initially learn to access it themselves.